2016
DOI: 10.17576/jskm-2016-1402-12
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Management in Fluoroscopy Procedures: Less is More?

Abstract: The aims of this study are (1) to determine the scattered radiation dose levels in routine fluoroscopy procedures and (2) to compare them with the equivalent chest x-rays and also (3) to monitor common techniques and radiation safety measures taken by the medical officers. The study covered a sample of 105 fluoroscopic procedures performed by 18 medical officers. Each officer wore a personal pocket dosimeter inside the lead gown during each procedure. A digital dosimeter was placed near the detector of the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A Malaysia study revealed that the average distance to the nearest public health care facility was approximately double that of the wealthiest quintile. 9 The strength of this study is that it was conducted in a state with a low GDP per capita and preponderance of BT hospitals that are representative of the population. It can be used to help ministries assess the effectiveness of their social health initiatives and the impact of the local infrastructure on patients with TDT, thereby reducing their OOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Malaysia study revealed that the average distance to the nearest public health care facility was approximately double that of the wealthiest quintile. 9 The strength of this study is that it was conducted in a state with a low GDP per capita and preponderance of BT hospitals that are representative of the population. It can be used to help ministries assess the effectiveness of their social health initiatives and the impact of the local infrastructure on patients with TDT, thereby reducing their OOP.…”
Section: Discussionmentioning
confidence: 99%
“…A Malaysia study revealed that the average distance to the nearest public health care facility was approximately double that of the wealthiest quintile. 9…”
Section: Discussionmentioning
confidence: 99%